The Effect of Subjecting Zoning Plan Changes to Annulment During an Active Lawsuit - Halil Altındağ (İstanbul Hukuk Mecmuası)
Both administrative and judicial system courts can only decide on matters that have been requested of them. However, administrative courts in practice make an exception to this rule, particularly for zoning plans. Accordingly, if the zoning plan concerning a lawsuit filed against said zoning plan changes while the lawsuit is still ongoing and the new plan contains the same illegalities that were the subject of the first lawsuit, then the court hearing the case will also assess the legality of the new plan in the same proceedings. The Council of State decides whether a zoning plan that has been subjected to a lawsuit is to change while the lawsuit is ongoing. If so, an expert examination of the new plan should be made, and the new plan should be investigated as to whether the reason the original lawsuit had been filed exists in the same way in the new plan. Again, if so, the lack of an examination in this direction should be considered as a reason for annulment. Of course, although annulment of the second plan is not clearly stated in the judgment, this second plan also being unlawful is clearly understood based on the trial and the reasoning of the judgment. This is because the courts include the second plan in the evaluation on the grounds that the second plan is essentially a continuation of the first plan, that the contents of the plan are the same in terms of the subject matter of the case, and that the second plan cannot be accepted once the first plan has been abolished. In cases of unlawfulness, the courts are to decide to annul the second plan.